Employee Watchlist as an Effort to Prevent Fraud in Banking in Indonesia - Putra, Adirama Chrisna; Hamzani, Umianty; Fahmi, Muhammad; Helmi, Syarif M; Dosinta, Nina Febriana (STMIK Widya Cipta Dharma, 2025)
This study aims to develop a data-based Employee Watchlist system as a fraud prevention strategy in the banking sector in Indonesia. This study is based on the Fraud Triangle Theory, focusing on two main elements, namely motivation and opportunity, and strengthening the implementation of the Know Your Employee (KYE) strategy as regulated in POJK No. 12 of 2024 concerning Anti-Fraud Strategy. The method used is a case study with a descriptive-quantitative approach at Bank ABC. The data analyzed includes internal employee indicators such as Debt Service Ratio (DSR), leave patterns, and length of service in one position. The results of the study indicate that employees with DSR> 70%, do not take block leave, and hold the same position for more than two years have a high risk of fraud. This study supports the preparation of an Employee Watchlist system that is integrated with individual risk indicators predictively. This study also contributes to designing data-based supervision of employee behavior as part of the transformation of human resource risk management in the financial sector.